Control of Wind Energy Conversion Systems Based on the Modular Multilevel Matrix Converter - Rojas-Lobos, F; Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2017)
The nominal power of single wind energy conversion systems (WECS) has been steadily increasing, now reaching power ratings close to 10 MW. In the power conversion stage, medium-voltage power converters are replacing the conventional low-voltage back-To-back topology. Modular multilevel converters have appeared as a promising solution for multi-MW WECSs, due to their modularity and the capability to reach high nominal voltages. This paper discusses the application of the modular multilevel matrix converter to drive multi-MW WECSs. The modeling and control systems required for this application are extensively analyzed and discussed in this paper. The proposed control strategies enable decoupled operation of the converter, provide maximum power point tracking capability at the generator side, grid code compliance at the grid side (including low-voltage ride-Through control) and good steady state and dynamic performance for balancing the capacitor voltages in all the clusters. Finally, the effectiveness of the proposed control strategy is validated using simulation and through experimental results obtained with a 27-power-cell prototype. © 1982-2012 IEEE.